MerMade: An Oligodeoxyribonucleotide Synthesizer for High Throughput Oligonucleotide Production in Dual 96-Well Plates - Rayner, Simon; Brignac, Stafford; Bumeister, Ron; Belosludtsev, Yuri; Ward, Travis; Grant, O’dell; O’Brien, Kevin; Evans, Glen A.; Garner, Harold R. (Genome Research, 1998)
We have designed and constructed a machine that synthesizes two standard 96-well plates of oligonucleotides in a single run using standard phosphoramidite chemistry. The machine is capable of making a combination of standard, degenerate, or modified oligos in a single plate. The run time is typically 17 hr for two plates of 20-mers and a reaction scale of 40 nm. The reaction vessel is a standard polypropylene 96-well plate with a hole drilled in the bottom of each well. The two plates are placed in separate vacuum chucks and mounted on an xy table. Each well in turn is positioned under the appropriate reagent injection line and the reagent is injected by switching a dedicated valve. All aspects of machine operation are controlled by a Macintosh computer, which also guides the user through the startup and shutdown procedures, provides a continuous update on the status of the run, and facilitates a number of service procedures that need to be carried out periodically. Over 25,000 oligos have been synthesized for use in dye terminator sequencing reactions, polymerase chain reactions (PCRs), hybridization, and RT–PCR. Oligos up to 100 bases in length have been made with a coupling efficiency in excess of 99%. These machines, working in conjunction with our oligo prediction code are particularly well suited to application in automated high throughput genomic sequencing.